KAJIAN TENTANG MANUSIA - Arifan Ananda; Wedra Aprison (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This article delves into the fundamental components of educational scholarship, focusing on the concept of human nature within the realm of Islamic thought. Recognizing five key elements in educational studies—namely, the concept of humanity, educational goals, learners, educators, and the learning process—the article places particular emphasis on the concept of humanity. Human beings, considered unique and enigmatic creatures, possess the dual capacity to be educated (as learners) and to educate (as educators), making them central to the aims and processes of education. The article draws from various perspectives, including philosophical and Quranic viewpoints, to elucidate the profound nature of humanity. From a philosophical standpoint, ancient Greek philosophers such as Plato and Aristotle are invoked to explore the complexities of the human body and soul. Islamic philosophers like Ibn 'Arabi and Al-Farabi are also referenced to highlight the significance of human intellect and spirituality. In the context of Islam, the quest for self-discovery through intellectual capabilities becomes imperative. The Quranic perspective underscores the importance of contemplating one's essence and encourages seeking truth through reference to the Quran as the foundational framework for Islamic thought. Methodologically, this article adopts a literature review approach, specifically a critical descriptive analysis. Drawing from a range of educational experts' articles and journals, the research aims to unravel the Quranic perspective on the essence of humanity. The results and discussions section explores the linguistic and terminological origins of the term "human" in various languages, emphasizing the dual material and spiritual nature of human existence. Noteworthy philosophical perspectives from ancient Greek philosophers to Islamic scholars such as Al-Farabi are presented to underscore the intricacies of the relationship between the body and soul. The article also delves into the Quranic and Hadith narratives on the creation of humanity, elucidating the two stages of human creation: the first being the creation of the first human (Adam), and the second involving the descent of humanity from Adam. The Quranic verses and Hadith are cited to explain the intricate stages of human formation from clay to the infusion of the divine spirit, providing a comprehensive understanding of the process. In conclusion, this article offers a comprehensive exploration of the concept of human nature from philosophical and Quranic perspectives, shedding light on the profound nature of human existence and its significance in the realm of education.